Memory Songs Decrease Depression For Stroke Patients - Harmayetty Harmayetty; Ika Yuni Widyawati; Anggun Perwita Sari (Universitas Airlangga, 2008)
Introduction: Biological, physical and phsycosocial changes in stroke patient could be a stressor that induced a depression state. There would be an emotional disturbance in stroke patient and stroke attack would be recurrent, if it was not treated. One of the alternative techniques to reduce depression is musical therapy especially memory songs.Methods: This study was used a quasy experimental pre-post test purposive sampling design. The population was stroke patients who treated in Neurological Ward A and Stroke Unit Dr Soetomo Hospital Surabaya. There were 12 respondents divided into 6 respondents for treatment group and 6 respondents for control group. The independent variable was music (memory song) and dependent variable was depression. Data were collected by using questionnaire which adapted from Hamilton Depression Rating Scale and Geriatric Depression Rating Scale, then analyzed by using Wilcoxon Signed Rank Test and Mann Whitney U Test with significance level α≤0.05.Results: The result showed that there was a difference between pre test and post test in depression (p=0.0196) and there was a difference in the depression between treatment group and control group (p=0.002).Conclution: It can be concluded that music (memory songs) has an effect to the depression of stroke patient. Further studies are needed to concerning other factors that may affect the relaxation technique especially in listening music.